Intranasal splints (INS)using an empty intravenous fluid bottles, Effectiveness and morbidity . - Nuseir, Amjad; al Omari, ahmad; Alzoubi, Firas; Ezuraiqi, Bassam (Jordan Medical Journal, 2016)
Abstract: Objective : The study was carried out to evaluate the effect of customized Intranasal splints (INS) using an empty I.V fluids bottles after septoplasty procedures, in terms of patient’s tolerance, preventing post operative adhesions and associated morbidity. Design: Rretrospective study at a regional referral hospital between 2008 and 2012 in patients who underwent Septoplasty procedure without any other nasal surgery. INS using an empty I.V fluid bottle were inserted in randomly selected patients after surgery. No nasal packing was used for all patients . INS were removed on 7th post operative day in the clinic without anesthesia. Methods: sixty adults patients who underwent pure Septoplasty procedure were randomly categorized into two equal groups, one group with INS and the other group without . None of the patients had nasal packing. An empty I.V fluid bottles were used as INS , which is available, cheap and easy to cut in different sizes. post operative pain were evaluated by using a VAS at day one. At day 7 pain and discomfort were evaluated due to nasal splint removal and nasal cleaning comparing with only nasal cleaning and suctioning of the non-splinted group. Six weeks later, assessment was conducted for symptomatic improvement, septum stability, and the possible complications . The results: Our study results showed that Intranasal splints using an empty intravenous bottle is safe, well tolerated, cheap and has significantly decreased the risk of adhesions, without increasing risk of septal hematoma, infection or perforation, However, it had significantly increased the pain and nasal discomfort during removing them one week after surgery.